PERAN PENDIDIKAN DALAM PENGEMBANGAN KETERAMPILAN ABAD KE-21: TINJAUAN LITERATUR TENTANG KURIKULUM DAN METODE PENGAJARAN - Nur Rohman; Hendra SH (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
This research explores the role of 21st century skills in education, focusing on integration in the curriculum, evaluation of effectiveness, and implementation of innovative teaching methods. The research method used is literature review. The research results show that the integration of 21st century skills in the curriculum is crucial for maintaining educational relevance. Evaluation of curriculum effectiveness is important to assess the achievement of 21st century skills development goals. Project-based curriculum approaches, contextual learning, and critical and creative teaching methods have great potential in developing students' holistic skills. Despite challenges such as resistance to change, research findings identify opportunities for improvement. Parent involvement, industry-education collaboration, and optimizing collaboration between educators can increase the effectiveness of curricula and teaching methods. This research emphasizes the urgency of deeply understanding the role of curriculum and teaching methods in shaping 21st century skills. By overcoming challenges and exploiting opportunities, education can be a transformational force in preparing individuals for the demands of the modern world.